Aqmarithm Enterprise / Nur Hadirah Abdul Salam - Abdul Salam, Nur Hadirah (2020)
Regarding to fulfil Fundamental of Entrepreneurship (ENT300) course requirement, I have to carry out a case study about sole proprietorship or partnership business. During the case study, I am entrusted to collect and review all information and resources related to the Aqmarithm Enterprise to complete the task. Therefore, I decided to interview the company virtually due to the world situation that is severely affected by the covid-19 pandemic. I was interview the founder itself, Nurul Aqmar binti Mohd Ismail. From the interview session, I have known her company’s background, organizational chart, characteristics of founder and collection of products. Besides that, I am also enable to analyses the business entity through SWOT (strengths, weakness, opportunities, threats) and get to know about her business achievements. At the first, her small business is not well-known in Malaysia and she was struggling at that time to improve the business itself. Then, she encourage her best friend to join together in handling this business and be a part of the Aqmarithm Enterprise. Due to her efforts and patience, her small business become successful and getting known by people through social media such as Instagram, Facebook and the new one is Tik Tok.